The Adoption of WhatsApp: Breaking the Vicious Cycle of Technological Poverty in South Africa - Shambare, Richard (Journal of Economics and Behavioral Studies, 2014)
Although research clearly demonstrates that consistent technology usage is correlated to socioeconomic development, the Vicious Cycle of Technology Affordability and Non-adoption impedes the uptake of ICTs in many developing countries. In South Africa, however, one Smartphone messaging application, WhatsApp, appears to have broken this vicious cycle. This paper argues that, given that promoting the uptake of ICTs is a developmental imperative for emerging economies, studying the adoption and diffusion patterns of WhatsApp provides invaluable insights into ICT usage within the context of a developing country. This study modelled the factors influencing the adoption of WhatsApp among South African youths. Some 192 students participated in the study by means of a self-completion questionnaire developed from the Technology Acceptance Model. Structural equation modelling tested the proposed theoretical model. Results suggest that a combination of cost efficiency, simplicity, userfriendly features, and the ability to run on multiple platforms influences and promotes users’ attitudes and behavioural intentions to adopt WhatsApp.